Global Publication Trends and Research Hotspots of The Gastric Neuroendocrine Neoplasms: A Bibliometric Analysis of The Current Situation - Köseoğlu, Hüseyin; Kaya, Muhammed; Durak, İbrahim; Düzenli, Tolga; Kaymazlı, Mustafa; Sezikli, Mesut (European Journal of Therapeutics, 2024)
Objective: Gastric neuroendocrine neoplasms (gNENs) are uncommon tumors, with growing understandings about the disease. Bibliometric analyzes have the advantage of visually depicting the dynamic evaluation of scientific knowledge of a specific topic. The aim of this study was to perform and report bibliometric analysis of gNENs, which was not formerly studied in the literature. Methods: Articles published between 1980 and 2022 within the database of Web of Science Core Collection were included in this bibliometric analysis. Vosviewer package program and Datawrapper were used for bibliometric data interpretation. Results: A total of 2270 articles about gNENs was detected with 63240 citations and an H index of 103. A remarkable increase was detected among the articles for years. Research have focused on gastroenterology and hepatology, endocrinology and metabolism, oncology, general medicine, pathology and surgery areas. Norwegian University of Science Technology was the leading institution about gNENs literature. Modlin IM, had the highest number of articles and citations among the authors. United States, Japan and Italy were the top three countries with the most published articles. Conclusion: This bibliometric study provides an engrossing, insightful conclusion to the research and development trajectory in gNENs with a future perspective.